1987
DOI: 10.1002/pssa.2211010208
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure and transport properties of Me6M2O11 (Me:Sr, Ba; M:Nb, Ta)-type phases

Abstract: Electrical conductivity and ion transfer numbers in complex oxides of Me6M2O11(Me:Sr, Ba; M: Nb, Ta) type and solid solutions based on them are investigated. The high mobility of oxygen ions is shown to be due to oxygen structural vacancies V ×S, and the decrease in ion conductivity in Me6M2O11–Me4M2O9 solid solutions is caused by the appearance of M Me…‐type substitutional defects and simultaneous filling of oxygen structural vacancies. The model of solid solution formation is corroborated by picnometric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…We may thus, conclude that the present conductivity is essentially ionic, at least, for the compound with x = 0.103. Previous studies also showed that the ionic contribution was found to dominate over the electronic contribution in the wide ranges of oxygen partial pressures for the compounds with x = 0.0667 and x = 0.2733 . Therefore, it is likely that the total conductivities measured in air for the compounds presented here were predominantly due to ionic.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…We may thus, conclude that the present conductivity is essentially ionic, at least, for the compound with x = 0.103. Previous studies also showed that the ionic contribution was found to dominate over the electronic contribution in the wide ranges of oxygen partial pressures for the compounds with x = 0.0667 and x = 0.2733 . Therefore, it is likely that the total conductivities measured in air for the compounds presented here were predominantly due to ionic.…”
Section: Resultssupporting
confidence: 50%
“…A proper variation of composition in the B sublattice for given oxidation states of metal ions allows a variation of oxygen deficiency in the structures. It is the case for A II 4 (A II 2–2 x B V 2+2 x )O 11+3 x or A II 6–2 x B V 2+2 x O 11+3 x type structures, where A represents alkaline earth metals and B niobium or tantalum atoms. Many of these compounds displayed predominant oxide ion conductivity at high temperatures, as well as a proton conductivity at lower temperatures under wet atmospheres. …”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the heterogeneous mixing of starting precursors. Based on the thermal analysis and previous literature data [25] all the K doped SSN samples are calcined at 1000°C for 2 h and checked for phase purity. .…”
Section: Resultsmentioning
confidence: 99%
“…Until now however, only a few materials have been proposed as electrolytes for SOFC, most of them are simple perovskites suitably doped to get the required property such as: Sr doped LaGaO 3 [9,10], (La,Sr)(Ga,Mg)O 3−δ [11], Ce 0.9 Gd 0.1 O 1.95 [12] and La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 2.8 [13]. Commonly used ceramic SOFC electrolytes are Scandium doped zirconia (SDZ), Gadolinium doped Ceria (GDC) and Bismuth Yttrium Oxide (BYO) [14] ) is a type of perovskite oxide reported to be good proton conductor with reasonable conductivity (∼10 −1 S cm −1 ) [25] and can be used as promising material for sensors and SOFCs [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation